2007
DOI: 10.1093/schbul/sbm095
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Reducing Duration of Untreated First Psychosis: Information Campaigns

Abstract: Intensive education campaigns toward the general public, the schools, and the primary health care services appear to be an important and necessary part of an early detection program. When such a campaign was stopped, there was a clear regressive change in help-seeking behavior with an increase in DUP and baseline symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(201 citation statements)
references
References 16 publications
(15 reference statements)
6
191
1
3
Order By: Relevance
“…The sample was recruited as part of the on-going TIPS 2 study (Early Treatment and Intervention in Psychosis) that commenced in 2002 15 and included persons experiencing a FEP. All participants completed baseline clinical assessment for TIPS 2 (see Joa et al 15 for details of method and assessment tools).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was recruited as part of the on-going TIPS 2 study (Early Treatment and Intervention in Psychosis) that commenced in 2002 15 and included persons experiencing a FEP. All participants completed baseline clinical assessment for TIPS 2 (see Joa et al 15 for details of method and assessment tools).…”
Section: Methodsmentioning
confidence: 99%
“…All participants completed baseline clinical assessment for TIPS 2 (see Joa et al 15 for details of method and assessment tools). The project was approved by the Regional Committee for Medical Research Ethics Health Region West, Norway (015.03).…”
Section: Methodsmentioning
confidence: 99%
“…Reducing the duration of untreated psychosis is, therefore, an important aim. Research has shown that combining awareness-raising campaigns with a readily available FEP service leads to a significant reduction in the duration of untreated psychosis (Joa et al, 2008).…”
Section: Ebr Iii-1mentioning
confidence: 99%
“…[48,49] Joa et al [50] found in their study that the use of intensive information campaigns, educating the general public about the early signs and symptoms of schizophrenia and the importance of early intervention, significantly reduced DUPs, which raises the hope that educational efforts could have a positive impact on reducing DUP in the southeast Nigeria population. In the Nigerian context, therefore, such campaigns should, among other things, target traditional and faith healers in order to reduce the DUP and improve treatment outcomes for patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 98%